Virtual Reality as a Tool for Teaching Children with Special Needs - Rizwan Faris Syafiq; Hafiz Hakim (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Virtual reality (VR) has shown significant potential in creating engaging and therapeutic learning environments for children with special needs. This paper investigates the use of VR technology in special education to enhance sensory experiences, cognitive skills, and social interaction. Case studies and research findings highlight how VR can be tailored to meet the unique learning needs of children with autism, ADHD, and other developmental disorders.